A contribuição do modelo de excelência em gestão pública no processo de aprendizagem organizacional da Embasa - Santana, Roberta Silva de Carvalho (2009)
Public and private organizations are inserted in a high competitive environment, so that the need to maintain themselves has made them to adopt the learning as strategic process. Considering this context, the public organizations started to realize the need to modernize public management. That is when appeared the Brazilian Public Management Movement the Programa Nacional de Gestão Pública Gespública , a national public management program which uses a methodology based in learning called Excellence in Public Management Model which encourages organizations to systematically evaluate their management practices to implement improvements. This way, in this dissertation we have attempted to analyse how the Excellence in Public Management Model collaborates to learning process, using a public water supply and sanitation company (known as Embasa) as an experimental unit. Beyond that, we have tried to identify learning organizations facilitator factors and understand Excellence in Public Management Model influences in Embasa learning process. This research justifies itself because represents an additional analysis to learning studies due to new modern State configuration, which still are superficial. Based on this job, we have concluded that the Public Management Excellence Model has indeed collaborated to Embasa learning process, once it has implemented practices that enlarge the organization way of learning. Before using the model, learning moments were limited to the company training program but, after the excellence model, people started to see that there are many other ways to access knowledge as when they make part of activities which involves experiences changing, carrying out practices, interaction and reflection, such as done by committees, work groups and mentoring.